2008
DOI: 10.1097/nmd.0b013e31815faa2b
|View full text |Cite
|
Sign up to set email alerts
|

The Dysexecutive Questionnaire Advanced

Abstract: The Dysexecutive Questionnaire (DEX, , Behavioral assessment of the dysexecutive syndrome, 1996) is a standardized instrument to measure possible behavioral changes as a result of the dysexecutive syndrome. Although initially intended only as a qualitative instrument, the DEX has also been used increasingly to address quantitative problems. Until now there have not been more fundamental statistical analyses of the questionnaire's testing quality. The present study is based on an unselected sample of 191 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 14 publications
2
24
0
1
Order By: Relevance
“…Furthermore, DEX has two versions, self- and informant-reported questionnaires. In other studies using DEX, sometimes only the self-reported version (Amieva et al 2003; Bodenburg and Dopslaff 2008; Heffernan et al 2004) and sometimes only the informant-reported version (Chaytor and Schmitter-Edgecombe 2007; Krabbendam et al 1999) was used, yet in other cases both versions were used (Burgess et al 1998; Odhuba et al 2005). Some studies have reported that the informant-reported version correlated better with psychological measures, such as other executive functions, general cognitive functions, and perception, than the self-reported version (Burgess et al 1998; Evans et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DEX has two versions, self- and informant-reported questionnaires. In other studies using DEX, sometimes only the self-reported version (Amieva et al 2003; Bodenburg and Dopslaff 2008; Heffernan et al 2004) and sometimes only the informant-reported version (Chaytor and Schmitter-Edgecombe 2007; Krabbendam et al 1999) was used, yet in other cases both versions were used (Burgess et al 1998; Odhuba et al 2005). Some studies have reported that the informant-reported version correlated better with psychological measures, such as other executive functions, general cognitive functions, and perception, than the self-reported version (Burgess et al 1998; Evans et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The Dysexecutive Questionnaire (DEX) (42) is a rating tool with participant and surrogate forms, which assesses behaviors mediated by executive functioning such as decision-making, impulsivity, social appropriateness, and planning for the future. Though the psychometric properties of the DEX have been relatively little studied, recent investigations have demonstrated it to be a reliable measure (r = 0.85) (52). …”
Section: Methodsmentioning
confidence: 99%
“… DEX, Dysexecutive Questionnaire [35]; MMSE, Mini-mental State Exam [36]; TUG, Timed Up-and-Go Test [37]; ADL, Activities of Daily Living [11]; FAQ, Functional Activities Questionnaire [38]; EQ-5D, European Quality of Life-5 Dimensions Visual Analog Scale [39]. …”
Section: Figurementioning
confidence: 99%